We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
21
1
avatar

For a certain arithmetic progression, the sum of the first 1729 terms is equal to the sum of the first 29 terms.  Find, with proof, the sum of the first 1758 terms.  Show all your steps!

 Dec 3, 2019
 #1
avatar+23575 
+2

For a certain arithmetic progression, the sum of the first 1729 terms is equal to the sum of the first 29 terms. 

Find, with proof, the sum of the first 1758 terms. 

Show all your steps!

 

Formula arithmetic progeression: \(a_n = a_1 + (n-1)d\)

 

\(\begin{array}{|rcll|} \hline s_{1729} &=& \left(\dfrac{a_1+a_{1729}}{2}\right)*1729 \quad & | \quad a_{1729} = a_1 + 1728d \\ s_{1729} &=& \left(\dfrac{a_1+a_1 + 1728d}{2}\right)*1729 \\ s_{1729} &=& \left(\dfrac{2a_1+ 1728d}{2}\right)*1729 \quad & | \quad \text{the sum of the first 1729 terms} \\ \hline \end{array} \)

\(\begin{array}{|rcll|} \hline s_{29} &=& \left(\dfrac{a_1+a_{29}}{2}\right)*29 \quad & | \quad a_{29} = a_1 + 28d \\ s_{29} &=& \left(\dfrac{a_1+a_1 + 28d}{2}\right)*29 \\ s_{29} &=& \left(\dfrac{2a_1+ 28d}{2}\right)*29 \quad & | \quad \text{the sum of the first 29 terms} \\ \hline \end{array} \)

 

\(\mathbf{s_{1729}=s_{29}}\)

\(\begin{array}{|rcll|} \hline \mathbf{s_{1729} } &=& \mathbf{s_{29}} \\\\ \left(\dfrac{2a_1+ 1728d}{2}\right)*1729 &=& \left(\dfrac{2a_1+ 28d}{2}\right)*29 \\ \left( 2a_1+ 1728d \right)*1729 &=& \left( 2a_1+ 28d \right)*29 \\ 2*1729a_1+1728*1729d &=& 2*29a_1+28*29d \\ 2a_1(1729-29) &=& (28*29-1728*1729)d \\ 2a_1*1700 &=& -2986900d \\ 2a_1*17 &=& -29869d \\ \mathbf{ 2a_1 } &=& \mathbf{-1757d} \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline s_{1758} &=& \left(\dfrac{a_1+a_{1758}}{2}\right)*1758 \quad & | \quad a_{1758} = a_1 + 1757 \\ s_{1758} &=& \left(\dfrac{a_1+a_1 + 1757d}{2}\right)*1758 \\ s_{1758} &=& \left(\dfrac{2a_1+ 1757d}{2}\right)*1758 \quad & | \quad \text{the sum of the first 1758 terms} \\ && \boxed{\mathbf{ 2a_1 = -1757d}} \\ s_{1758} &=& \left(\dfrac{-1757d+ 1757d}{2}\right)*1758 \\ s_{1758} &=& \left(\dfrac{0}{2}\right)*1758 \\ \mathbf{s_{1758}} &=& \mathbf{0} \\ \hline \end{array}\)

 

The sum of the first 1758 terms is 0.

 

laugh

 Dec 3, 2019

29 Online Users

avatar